Morphological Description and Histological Structure of Adrenal Gland in Black Iraqi Partridge Francolinus francolinus - Ahmed, Nusaibah Amer; Dauod, Hussain A.M. (Iraqi Journal of Science, 2023)
The objective of this study was to investigate the morphological description and histological structure of adrenal gland in Iraqi black partridge Francolinus francolinus from Iraqi environment. Twenty adult healthy birds (male and female) were used in present study. They were measured and adrenal glands were removed, measured and fixed by 10% formalin and formalin and chromate fixative then stained with rotein histochemical stain (Harris hematoxylin and eosin stain (H&E), periodic acid Schiff (PAS), Azan and Mallory stain). The partridge had a small couple of adrenal glands of yellow colour they are located in abdominal cavity nearby the margin of superior kidney lobe. These are small, ovoid glands lying just cranial to the kidneys and gonads on either side of the aorta and posterior vena cava. There was no difference in shapes between adrenal gland of male and female. There were no significantly differences in the measurement of the right and left adrenal gland of the partridge. Histologically the adrenal gland of partridge was mainly compose capsule of dense connective tissue, the thickness of capsule increased according to the different point of blood vessels and large nerve trunk, nerve cell bodies and chromaffin cell embedded in connective tissue, and the cortex is composed of three zones: zona glomerulosa, zona fasciculata, and zona reticularis, these zones were interfered with others. The cells of Zona glomerulosa were arranged in irregular ovoid clusters, the nuclei stain strongly, and the cytoplasm is less pale than that of the next zone, zona fasciculata, The secretary cells were arranged in cords, the nuclei of these cells stain strongly, and the cytoplasm looks pale due to the presence of lipid droplets. The cytoplasm of Zona reticularis stained more darkly, and contains fewer lipid droplets. However the layer of gland where interfered together without clear zone contain sinusoid capillary blood vessels extend from capsular region to medulla whih contain basophilic staining cells, with a granular cytoplasm and no stored lipid. Medullary cells were found between the large and comparatively dark cells of the cortex